Complementary and Alternative Medicine Use and Symptom Burden in Women Undergoing Chemotherapy for Breast Cancer in Malaysia - Chui, Ping Lei; Abdullah, Khatijah Lim; Wong, Li Ping; Mohd Taib, Nur Aishah (Lippincott, Williams & Wilkins, 2018)
Background: Complementary and alternative medicine (CAM) is commonly used for cancer- and chemotherapy-related symptoms. Nurses are likely to encounter many CAM users in their practice. Objective: The aims of this study were to assess CAM use and examine the symptom burden of CAM and non-CAM users among patients with breast cancer who are undergoing chemotherapy. Methods: A CAM use questionnaire and the Side-Effect Burden Scale were administered to 546 patients. Complementary and alternative medicine use was categorized as mind-body practices (MBPs), natural products (NPs), or traditional medicine (TM). Results: We identified 386 CAM users (70.7%) in this study. The CAM users reported a higher marginal mean total symptom burden score (40.39 ± 2.6) than non-CAM users (36.93 ± 3.21), although this difference was not statistically significant (P =.09). Triple-modality (MBP-NP-TM) CAM users had a significantly higher marginal mean total symptom burden score (47.44 ± 4.12) than single-modality (MBP) users (34.09 ± 4.43). The risk of having a high total symptom burden score was 12.9-fold higher among the MBP-NP-TM users than among the MBP users. Conclusions: Complementary and alternative medicine use is common among Malaysian patients who are undergoing chemotherapy for breast cancer. However, CAM and non-CAM users reported similar symptom burdens, although single-modality use of MBP is likely associated with a lower symptom burden. Implications for Practice: Nurses should keep abreast of current developments and trends in CAM use. Understanding CAM use and the related symptom burden will allow nurses to initiate open discussion and guide their patients in seeking additional information or referrals for a particular therapy.